EFFECT OF DOWN-HOLE LITHOLOGICAL VARIATION ON WATER BEARING CAPACITY OF SOME BOREHOLES IN ILORIN, NIGERIA - IROYE, Kayode Ademola (Studia Universitatis Babeș-Bolyai Geographia, 2021)
The paper attempts to explain the effect of downhole lithological variation on water bearing capacity of some boreholes in Ilorin Nigeria. Specifically, the study examined the lithological characteristics of the boreholes, assessed the variability in weathered overburden and analyzed the inter-relationships between lithology, hydrology and topography of the boreholes. Data used were extracted from twenty (20) borehole logs collected from the archive of Lower Niger Basin Development Authority in Ilorin. Information extracted from the borehole logs are: the number of lithological units intersected by each of the borehole and their depths, the nature of geological materials making up the lithological units and their moisture conditions. Information on coordinates and topographic heights of the boreholes are not given on the logs and those were collected from the field personally by the researcher using handheld GPS (Garmin GPS Channel 76 Model). The collected data were analyzed using descriptive statistics. Results reveal nine downhole lithological units with loamy and lateritic soil making up the first layer of lithology in 95% of the boreholes. Thickness of the top soil and the saprolite overlying the bedrock, has mean values of 4.2m and 11.3m respectively. Depth to water in the borehole ranged between 24.7 and 140m and with a mean value of 55.9m. Three (3) of the boreholes have two lenses of aquifer while the remaining seventeen (17) have one aquifer lens each. The three (3) boreholes with two aquifer lenses have their minor aquifers located within the saprolite. The main aquifer in most (65%) of the boreholes is located within the fractured basement while the remaining (35%) boreholes have their main aquifer located in the weathered basement. Correlation analysis revealed topographic elevation as one of the drivers of hydrology in the study area.